2020
DOI: 10.1080/2162402x.2020.1746138
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of CD73 expression in resected colorectal cancer liver metastasis

Abstract: Immune checkpoint blockade has not yet been effective in patients with mismatch repair proficient metastatic colorectal cancer. Targeting immunosuppressive metabolic pathways is being explored as a new immunotherapeutic approach. We assessed whether CD73, the rate limiting enzyme that catalyzes the degradation of extracellular AMP into immunosuppressive adenosine, could be an immunological determinant of colorectal liver metastases (CRLMs). By immunofluorescence on tissue microarrays, intratumoral CD73 express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…Furthermore, both enzymes regulate the magnitude of the purinergic reaction surrounding the immune cells. High expression of CD73 is therefore associated with low levels of lymphocytes in the TME and poor prognosis in for example colorectal, prostate, and triple-negative breast cancer [ 44 47 ]. Of note, CD73 is regulated by HIF-1alpha and therefore more abundant in a hypoxic microenvironment [ 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, both enzymes regulate the magnitude of the purinergic reaction surrounding the immune cells. High expression of CD73 is therefore associated with low levels of lymphocytes in the TME and poor prognosis in for example colorectal, prostate, and triple-negative breast cancer [ 44 47 ]. Of note, CD73 is regulated by HIF-1alpha and therefore more abundant in a hypoxic microenvironment [ 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29] Recently published data from patients with colorectal cancer liver metastases show that high levels of soluble CD73 expression are associated with shorter survival. 21 These results indicate that soluble CD73 may serve as a non-invasive blood-based biomarker of cancer outcome. Yet, it is unclear whether soluble CD73 is a clinically useful biomarker of prognosis and response to immunotherapy in patients with melanoma.…”
Section: Discussionmentioning
confidence: 81%
“…Overexpression of CD73 has been demonstrated to be correlated with poor clinical outcomes in diverse cancers ( 9 - 13 , 20 , 21 ). In a cohort of 902 patients with gastric cancer, CD73 expression was more intensive in gastric cancer tissues and patients with high levels of CD73 had significantly poorer OS and DFS ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…The role of CD73 in different cancer cells has been also widely studied. It’s indicated that high expression of CD73 is associated with poor prognosis in various cancers, including melanoma ( 9 ), papillary thyroid carcinoma ( 10 ), hepatocellular carcinoma ( 11 ), triple-negative breast cancer ( 12 ), and colorectal cancer ( 13 ). For RCC, a recently study also showed that high CD73 expression portended significantly worse disease-free survival (DFS) and overall survival (OS), indicating that CD73 might be a potent therapeutic target for RCC patients ( 14 ).…”
Section: Introductionmentioning
confidence: 99%